Deep learning detects retropharyngeal edema on MRI in patients with acute neck infections - Rainio, Oona; Huhtanen, Heidi; Vierula, Jari-Pekka; Nurminen, Janne; Heikkinen, Jaakko; Nyman, Mikko; Klén, Riku; Hirvonen, Jussi (Springer Nature, 2026)
Background
In acute neck infections, magnetic resonance imaging (MRI) shows retropharyngeal edema (RPE), which is a prognostic imaging biomarker for a severe course of illness. This study aimed to develop a deep learning-based algorithm for the automated detection of RPE.
Methods
We developed a deep neural network consisting of two parts using axial T2-weighted water-only Dixon MRI images from 479 patients with acute neck infections annotated by radiologists at both slice and patient levels. First, a convolutional neural network (CNN) classified individual slices; second, an algorithm classified patients based on a stack of slices. Model performance was compared with the radiologists’ assessment as a reference standard. Accuracy, sensitivity, specificity, and area under receiver operating characteristic curve (AUROC) were calculated. The proposed CNN was compared with InceptionV3, and the patient-level classification algorithm was compared with traditional machine learning models.
Results
Of the 479 patients, 244 (51%) were positive and 235 (49%) negative for RPE. Our model achieved accuracy, sensitivity, specificity, and AUROC of 94.6%, 83.3%, 96.2%, and 94.1% at the slice level, and 87.4%, 86.5%, 88.2%, and 94.8% at the patient level, respectively. The proposed CNN was faster than InceptionV3 but equally accurate. Our patient classification algorithm outperformed traditional machine learning models.
Conclusion
A deep learning model, based on weakly annotated data and computationally manageable training, achieved high accuracy for automatically detecting RPE on MRI in patients with acute neck infections.
Relevance statement
Our automated method for detecting relevant MRI findings was efficiently trained and might be easily deployed in practice to study clinical applicability. This approach might improve early detection of patients at high risk for a severe course of acute neck infections.
Key Points
​​​​​​​Deep learning automatically detected retropharyngeal edema on MRI in acute neck infections.
Areas under the receiver operating characteristic curve were 94.1% at the slice level and 94.8% at the patient level.
The proposed convolutional neural network was lightweight and required only weakly annotated data.